Effect of Harvesting Time and Wax Coating on Deterioration Rate of ‘Pondoh’ Snake Fruit Stored at Room Temperature - Santosa, Budi (Jurnal Teknologi Pertanian, 2007)
Snake fruit, known to have a high respiratory rate, is a perishable product with a shelf life of 6-7 days. For fresh consumption, the fruit is usualy harvested when it is fully mature. This research was aimed to determine an optimum harvesting time and to elucidate the effect of wax coating on quality changes during storage at room temperature. The harvesting was conducted at 5, 6 and 7 month after pollination. The harvested fruit was observed for the fruit morphological and sensoric characteristics and the total soluble solid, total acids, vitamin C and moisture contents. The fruits at certain degrees of maturity were selected for further wax coating treatment. The selected degree of maturity fruits was wax coated (10%) and and compared the changes with the uncoated one during storage at room temperature. The changes in sensoric characteristics (freshness, off-odour) and physico-chemical aspects of the fruits: total acidity, reducing sugars, fruit hardness during storage were observed. The results showed that the optimum time of harvesting the snake fruit was 6 months. Wax coating definitely extended the shelflife of the fruit up to 2 ( two) weeks. It was partly due to the inhibition of the declining of sugars and tannins.Keywords : harvesting time, wax coating, snake fruit var. pondoh